Differences in the expression of soluble proteins in freshwater and brackish‐water ecotypes of the snail Theodoxus fluviatilis. Issue 3 (22nd August 2022) - Wiesenthal, Amanda Alice; Müller, Christian; Albrecht, Dirk; Hildebrandt, Jan‐Peter
Abstract: The neritid snail Theodoxus fluviatilis has formed regional subgroups in northern Europe, where it appears in both freshwater (FW) and brackish water (BW) in coastal areas of the Baltic Sea. These ecotypes show clear differences in osmotolerance and in the modes of accumulating organic osmolytes under hyperosmotic stress. We reasoned that the expression patterns of soluble proteins in the two ecotypes may differ as well. BW snails have to deal with a higher salinity (up to 20‰) than FW snails (0.5‰) and also cope with frequent fluctuations in environmental salinity that occur after heavy rains or evaporation caused by extended periods of intense sunshine. Therefore, the protein expression patterns of specimens collected at five different FW and BW sites were analyzed using 2D SDS‐PAGE, mass spectrometry, and sequence comparisons based on a transcriptome database for Theodoxus fluviatilis . We identified 89 differentially expressed proteins. The differences in the expression between FW and BW snails may be due to phenotypic plasticity, but may also be determined by local genetic adaptations. Among the differentially expressed proteins, 19 proteins seem to be of special interest as they may be involved in mediating the higher tolerance of BW animals towards environmental change compared with FW animals.